A history of the expansion of Christianity ; v. 4 the great century in Europe and the United States of America A.D. 1800-A.D. 1914 - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1971)
Includes bibliographical references and index.
First published 1941, Harper and Row, Publishers, New York.
Keywords: Church history -- 19th century -- United States; Church history -- 19th century -- Europe